Role of nail bed methotrexate injections in isolated nail psoriasis: conventional drug via an unconventional route. (10th April 2017) - Grover, C.; Daulatabad, D.; Singal, A.
Summary: Nail psoriasis can be a debilitating condition; however, in patients with isolated nail involvement, the use of toxic systemic therapies such as methotrexate may not be justified. We report on 4 patients (30 involved nails between them), who were treated with injections of methotrexate (0.1 mL of a 25 mg/mL solution) into the nail bed at 3‐weekly intervals. Mean baseline Nail Psoriasis Severity Index (NAPSI) was 4.77 (range 2–8, cumulative score 143; n = 30); dropping successively at each visit to 2.43 (range 0–4, cumulative score 73; n = 30) at 15 weeks. The decline in mean NAPSI from 4.87 to 2.17 was statistically significant ( P < 0.001; Friedman analysis). Reported adverse effects were pain, injection site pigmentation and nail bed haemorrhage. Administration of specific targeted therapy to the nail bed may help manage nail psoriasis effectively.